SYNERGY OF AKIDAH MORALS TEACHERS AND COUNSELING GUIDANCE TEACHERS IN CHARACTER DEVELOPMENT OF STUDENTS AT MADRASAH TSANAWIYAH ISLAMIC BOARDING SCHOOL YASRIB LAPAJUNG WATANSOPPENG - Muhammad Muhaimin; Muhammad Rusmin (International Conference on Social and Islamic Studies, 2021)
This research aims to find out the Synergy Communication of Aqidah Akhlak Teachers and Counseling Guidance Teachers in Character Development of Students at Madrasah Tsanawiyah Islamic Boarding School Yasrib Lapajung Watansoppeng and to find out the Synergy Coordination of Aqidah Akhlak Teachers and Counseling Guidance Teachers in Character Development of Students in Madrasah Tsanawiyah Islamic Boarding School Yasrib Lapajung Watansoppeng, and to find out the Supporting and Inhibiting Factors in Character Development of students at Madrasah Tsanawiyah Islamic Boarding School Yasrib Lapajung Watansoppeng. This type of research is qualitative which takes place at Madrasah Tsanawiyah Pondok Pesantren Yasrib Lapajung Watansoppeng. The data sources in this study were the principal, Aqidah Akhlak teachers, counseling guidance teachers, and students. The data collection methods used were observation, interviews, and documentation. The research instrument is a observation guideline and interview guidelines with data analysis including data reduction (data reduction), data display (data display) and conclusion drawing and verification (conclusion drawings/verifications). The validity of the data is done by data triangulation. The results of this study shows that; 1) The synergistic communication between  Aqidah Akhlak teachers and  counseling guidance teachers at Madrasah Tsanawiyah Pondok Pesantren Yasrib Lapajung Watansoppeng is not maximized, the form of communication carried out by teachers is not formal but only through casual or non-formal conversations; 2) Sinergy Coordination between Aqidah Akhlak teachers and counseling guidence teachers at Madrasah Tsanawiyah Pondok Pesantren Yasrib Lapajung Watansoppeng is not maximized, the coordination discussed is done outside the meeting, teachers work independently; 3) Factors supporting and inhibiting the character development of students. Supporting factors: cooperation between teachers and parents of students, adequate facilities and infrastructure, applicable rules and regulations. Inhibiting factors: lack of awareness of students, poor social environment, lack of attention and understanding of parents, and students' mindsets that are difficult to regulate. It implies that the Aqidah Akhlak teachers and counseling guidance teachers at Madrasah Tsanawiyah Pondok Pesantren Yasrib Lapajung Watansoppeng should always improve the synergy related to communication and coordination in character building of students. The results of this study were used as input to Akhlak teachers at Madrasah Tsanawiyah Pondok Pesantren Yasrib Lapajung Watansoppeng.